Detailed Spectroscopic and Structural Analysis of TiO2/WO3 Composite Semiconductors - Biborka Boga; István Székely; Zsolt Pap; Lucian Baia; Monica Baia (Journal of Spectroscopy)
WO3-TiO2 composite materials were obtained using commercial titania (Evonik Aeroxide P25) and hydrothermally crystallized WO3. Different ratios of TiO2/WO3 were investigated, starting at 1 wt.% of WO3 to 50 wt.%. The morphology of WO3 was of the star-like type, and its structure is basically composed of monoclinic crystalline phase. All spectroscopic characteristics of the composites and their derived data (band-gap energy value, light absorption threshold, and IR specific bands) directly varied with the increase of the WO3 content. However, the oxalic acid photodegradation achieved under UV light reached the highest yield for 24 wt.% WO3 content, a result that was attributed to the charge separation efficiency and the surface hydrophilicity. The latter mentioned reason points out the crucial importance of the surface quality of the investigated structure in photocatalytic tests.